Interaksionalisme Simbolik Antara Karyawan Yang Berbeda Etnis - Edison B. Hutapea (FISIP Universitas Bung Karno, 2018)
Abstract:Culture manifest itself in patterns and nature of forms of activity and behavior that serve as models for adjustment actions and communication styles which allows people to live in a certain level of technical development. Cultural sustanaible and present where, culture includes all affirmations of behaviors received during the life period. Culture is also recognized as form and structure form, physical form and social environment which influence how we can live. Each culture has its own way of moving, sitting, standing, lying, and making gestures, body languange is culturally conditioned and should be interpreted according to the cultural backgroud. It means, the understanding of a person’s attitude or action is only partially understood when it can cross the cultural barrier. In the new situations and it is not being understood in the process, we will very depended with the interpretaton to nonverbal communication, the further the cultural differences, the more chance that we will make a wrong interpretation. Key word: Symbolic interaction, Communication among different culture, Language. Abstrak Budaya menampakan diri dalam pola-pola dan alam bentuk-bentuk kegiatan dan perilaku yang berfungsi sebagai model-model bagi tindakan-tindakan penyesuaian diri dan gaya komunikasi yang memungkinkan orang-orang tinggal dalam suatu masyarakat disuatu lingkungan geografi tertentu pada suatu tingkat perkembangan teknis tertentu. Budaya berkesinambungan dan hadir dimana-mana, budaya meliputi semua peneguhan prilaku yang diterima selama periode kehidupan. Budaya juga terkenal sebagai bentuk dan struktur bentuk dan struktur fisik serta lingkungan sosial yang mempengaruhi kita hidup. Setiap budaya mempunyai caranya sendiri dalam bergerak, duduk, berdiri, berbaring, dan membuat isyarat, bahasa tubuh ditentukan oleh budaya dan harus diartikan menurut latar belakang budayanya. Artinya, pemahaman tentang suatu sikap atau tindakan seseorang hanya sebagian saja yang dimengerti bila melewati batas budaya. Dalam situasi yang baru dan belum dikenal di dalamnya kita akan sangat bergantung pada penafsiran tanda-tanda nonverbal, semakin jauh perbedaan budaya makin besar kemungkinan kita membuat kesalahan penafsiran. Kata Kunci : Interaksionalisme Simbolik, Komunikasi Antarbudaya, dan Bahasa. Key word: Symbolic interaction, Communication among different culture, Language.